The Effect of Silicate Ions on the Separation of Lithium From Geothermal Fluid - Lee, Junbeum; Chung, Eunhyea (Frontiers in Chemical Engineering, 2022)
In an enhanced geothermal system (EGS), geothermal energy in rocks with insufficient permeability or fluid saturation can be used by creating artificial geothermal reservoirs. Generally, EGS geothermal fluid contains high concentrations of total dissolved solids that originated from various geochemical reactions between the fluid in the reservoir and the minerals in the rock. For example, the concentration of lithium ions are measured approximately 150 mg/L, and several researchers have focused on the recovery of lithium in the geothermal fluid using various methods, one of which is liquid extraction. Solvent extraction has been used to recover lithium from various sources, and successful recovery efficiency have been attained. However, the geothermal fluid in EGS reservoirs contains high concentrations of SiO2, which might inhibit the selective recovery of lithium. Thus, in this study, two consecutive stages of solvent extraction were used to separate the lithium from the geothermal fluid that contained different concentrations of SiO2 ions. The divalent ions were removed in the first stage, and the lithium ions were extracted effectively in the second stage. The SiO2 inhibits the selective recovery of lithium in the first stage to a greater extent than it does in the second stage. Silicate ions can be problematic due to the formation of scaling in EGSs, so controlling its concentration in the geothermal reservoir would be beneficial for the long-term operation of EGSs and for the successful recovery of valuable metal resources from EGS reservoirs.